THE URGENCY OF CIVIC EDUCATION IN SHAPING DIGITAL CITIZENS' CHARACTER IN THE SOCIETY 5.0 ERA - Bambang Yuniarto; Ilham Ayudi Hidayah; Alya; Adelia Aisyah Ramadhani; Mindi Aprilia; Zakiyah Fitriani; Nayla Saidah (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This study aims to analyze the urgency of Citizenship Education in shaping the character of digital citizens in the Society 5.0 era, which is characterized by the integration of physical and digital spaces. Rapid technological transformation presents new challenges, such as the spread of hoaxes, moral degradation, and weak digital ethics, necessitating the strategic role of Citizenship Education in instilling Pancasila values, social responsibility, and ethical media awareness. This research employs a qualitative descriptive method through a literature study, analyzing various relevant national and international scholarly works on civic education, digital citizenship, and Society 5.0. The findings indicate that Citizenship Education plays a crucial role in forming intelligent, critical, and ethically-digital citizens by strengthening digital literacy, media ethics, and project-based learning with digital simulations. Furthermore, the study reveals that Citizenship Education learning must transform by integrating technology and national values to align with the demands of the digital era. The implications of this research affirm the necessity for a digital literacy-based Citizenship Education curriculum, enhancing teacher technological competency, and government policy support to strengthen digital character education. Thus, Citizenship Education does not only function as normative education but also serves as a strategic means of shaping civilized, responsible, and Pancasila-minded digital citizens.